A New Multicarrier Sinusoidal Pulse Width Modulation (SPWM) Strategy based on Rooted Tree Optimization (RTO) Algorithm for Reducing Total Harmonic Distortion (THD) of Switched-Capacitor Nine-level Inverter in Grid-connected PV systems - H. Aboub; R. Mechouma; B. Azoui; C. Labiod; A. Khechekhouche (Universitas Pendidikan Indonesia, 2022)
This paper proposed a new strategy of sinusoidal pulse width modulation (SPWM) technique to control three-phase nine-level switched-capacitor inverter (9LSCI) in grid-connected PV systems. The main advantage of this inverter is high voltage gain, achieved by switching the capacitors in series and parallel to boost up the output voltage using low voltage input. To improve the quality of solar energy for injection into the electrical grid, a rooted tree optimization (RTO) algorithm is used to get optimum values of initial angles of multi carriers SPWM technique, giving the lowest possible values of the total harmonic distortion (THD). The design also can maximize the efficiency of the multi-level inverter by minimizing its size using fewer components and a single DC source and reducing the rate of THD. The higher effectiveness and accuracy of the suggested RTO-SPWM technique was tested and verified in comparison to existing classical SPWM technique from the performance of PV-grid systems that it can effectively reduce the total harmonic distortion to 0.16 %.